Prospective study of the association between chronotype and cardiometabolic risk among Chinese young adults - Tingting Li; Yang Xie; Shuman Tao; Liwei Zou; Yajuan Yang; Fangbiao Tao; Xiaoyan Wu (BMC Public Health)
Abstract Background The association of evening chronotype with cardiometabolic disease has been well established. However, the extent to which circadian rhythm disturbances independently result in risk remains unclear. This study aimed to investigate the cross-sectional and prospective longitudinal associations between chronotype and cardiometabolic risk among Chinese young adults. Methods From April to May 2019, a total of 1 135 young adults were selected to complete the self-administered questionnaire, and 744 fasting blood samples were collected to quantify cardiometabolic parameters. From April to May 2021, 340 fasting blood samples were collected to quantify cardiometabolic parameters. The Morning and Evening Questionnaire 5 (MEQ-5) was used to assess chronotype. The cardiometabolic (CM)-risk score was the sum of standardized Z scores based on gender for the 5 indicators: waist circumference (WC), mean arterial pressure (MAP), triglyceride (TG), homeostasis model assessment for insulin resistance (HOMA-IR), and high-density lipoprotein cholesterol (HDL-C), where the HDL-C is multiplied by-1. The generalized linear model was used to determine the cross-sectional and prospective longitudinal associations between chronotype and each cardiometabolic parameter. Results Cross-sectional association analysis showed that lower MEQ-5 scores were correlated with higher fasting insulin (β=-1.420, 95%CI: -2.386~-0.453), higher HOMA-IR (β=-0.301, 95%CI: -0.507~-0.095), and higher CM risk score (β=-0.063, 95%CI: -0.122~-0.003), even after adjustment for covariates. Prospective longitudinal association analysis also showed that lower MEQ-5 scores were associated with 2 years later higher fasting glucose (β=-0.018, 95%CI: -0.034~-0.003), higher fasting insulin (β=-0.384, 95%CI: -0.766~-0.003), higher HOMA-IR (β=-0.089, 95%CI: -0.176~-0.002), and higher CM-risk score (β=-0.109, 95%CI: -0.214~-0.003) after adjustment for covariates. Conclusions Evening chronotype was significantly correlated with higher CM risk among young adults. Our findings suggest that biologically and socially affected sleep timing misalignment is a contributing factor to cardiovascular disease risk.